1990
DOI: 10.1042/bj2720099
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of glucose transport proteins in plasma membrane- and Golgi vesicle-enriched fractions prepared from lactating rat mammary gland

Abstract: Plasma membrane-and Golgi vesicle-enriched membrane fractions were prepared from day-10 lactating rat mammary glands. Each fraction was found to contain a single set of D-glucose-inhibitable cytochalasin B-binding sites: plasma membranes and Golgi vesicles bound 20+ 2 and 53 +4 pmol of cytochalasin/mg of membrane protein (means + S.E.M.), with dissociation constants of 259 + 47 and 520 + 47 nm respectively. Anti-peptide antibodies against the C-terminal region (residues 477-492) of the rat brain/human erythroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 42 publications
4
40
1
Order By: Relevance
“…In the rat mammary gland, a cell fractionation study suggested that GLUT1 or a related transporter might be present in the Golgi apparatus in addition to the plasma membrane [13]. It was suggested that the glucose transporter in the Golgi membrane may play an important role in supplying glucose for lactose synthesis within the Golgi lumen [13]. However, we were unable to demonstrate GLUT1 in the Golgi apparatus by immunofluorescence or immunoelectron microscopy using anti-GLUT1 antibody.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…In the rat mammary gland, a cell fractionation study suggested that GLUT1 or a related transporter might be present in the Golgi apparatus in addition to the plasma membrane [13]. It was suggested that the glucose transporter in the Golgi membrane may play an important role in supplying glucose for lactose synthesis within the Golgi lumen [13]. However, we were unable to demonstrate GLUT1 in the Golgi apparatus by immunofluorescence or immunoelectron microscopy using anti-GLUT1 antibody.…”
Section: Discussioncontrasting
confidence: 40%
“…GLUT1 localized at the basolateral domain in these metabolically active epithelial cells may serve for the uptake of glucose from the intercellular space of connective tissues adjacent to blood vessels. In the rat mammary gland, a cell fractionation study suggested that GLUT1 or a related transporter might be present in the Golgi apparatus in addition to the plasma membrane [13]. It was suggested that the glucose transporter in the Golgi membrane may play an important role in supplying glucose for lactose synthesis within the Golgi lumen [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is good evidence that glucose uptake by mammary epithelial cells for use during de novo fatty acid synthesis, as well as synthesis of lactose, is mediated by the glucose transporter, glucose transporter-1 (GLUT1). Expression of GLUT1 increases during lactation, and a change in its subcellular localization has been observed in mammary epithelial cells during lactation (14)(15)(16).…”
mentioning
confidence: 99%
“…Therefore the uptake of glucose and its transport across the basolateral membrane are important processes during milk synthesis. The glucose transporter (GLUT1) is present at the basolateral membrane of rodent MEC (Madon et al, 1990;Nemeth et al, 2000) and is the predominant glucose transporter in the lactating bovine mammary gland (Zhao and Keating, 2007). The expression of genes encoding the glucose transporters is under the control of lactogenic hormones in the mammary gland during pregnancy and lactation (Shennan and Peaker, 2000 and references therein; Zhao and Keating, 2007).…”
Section: Glucosementioning
confidence: 99%